Un giro hacia el cuerpo en la narrativa contemporánea: el caso particular de La comemadre de Roque Larraquy - Nemrava, Daniel (Verbum – Analecta Neolatina, 2021)
Our objective is to examine how Roque Larraquy’s novel, La comemadre, explores the “I” from the body, from the “flesh” itself, which literary figures of the body the author uses to narrate the effects of eccentricity in today’s society linked to the sinister, the violent and political. To formulate and delimit the problems of the body we take as a base, among other scholars, Jean-Luc Nancy’s reflections on the body, Erika Fischer-Lichte’s studies on the aesthetics of the performative, and Hans Belting’s anthropology of the image.